Liberalization of Health Services in Indonesia in The Context of Justice - Ramadhani, Fauziah (Semarang State University Undergraduate Law and Society Review, 2022)
Health is an important factor for maintaining living standards. In human rights which is explained in more detail, health is included in the rights of every human. That rights also includes right to get good health services. But in practice, the health services provided sometimes are not in accordance with what was been regulated in the code of ethics, obligation and violating human rights. This study compared one cases with another cases. We analyze the cases by comparing existing regulations, such as Indonesian constitution, health pofession ethics and hospital ethics. The study emphasized and found that in the Indonesian Constitution and the code of ethics there are no rules for distinguishing patients. In terms of health, all communities should be considered equal. Because this concerns human rights which say that health is an absolute right for every human being. The hospitals nd the staff who work in that hospitals can be threatened with criminal law or civil law. The study concluded that discrimination in helath services should not occur in Indonesia or in other countries. Because in Indonesia, health is the ideals and goals of Indonesian nation, and also an element of human rights. Health services in Indonesia must be based on Pancasila and based on humanitarian values, health ethics, professionalism, equality and anti-discrimination, equity and justice.